2001
DOI: 10.1677/joe.0.1700121
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 inhibits the expression of luteinizing hormone receptor mRNA during the maturation of cultured rat granulosa cells

Abstract: Interleukin-6 (IL-6) and its receptor components have been shown to be present in rat follicular granulosa cells. The present study was designed to examine the effect of this cytokine on changes in expression of the luteinizing hormone receptor (LHR) messenger RNA and of the steroidogenic enzyme, CYP11A1 (cytochrome P450 scc) in an in vitro model of granulosa cell maturation. Ovarian granulosa cells harvested from immature rats 2 days after treatment with equine chorionic gonadotropin were cultured for 48 h in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…There were several reports on the effect of IL‐6 on follicular development. In one report, the addition of IL‐6 into the rat granulosa cell culture medium inhibited LHR expression . In other reports, IL‐6 inhibited estradiol and progesterone production that were induced by FSH stimulation in the granulosa cells .…”
Section: Luteinizing Hormone Receptor Expression In the Granulosa Cellsmentioning
confidence: 99%
“…There were several reports on the effect of IL‐6 on follicular development. In one report, the addition of IL‐6 into the rat granulosa cell culture medium inhibited LHR expression . In other reports, IL‐6 inhibited estradiol and progesterone production that were induced by FSH stimulation in the granulosa cells .…”
Section: Luteinizing Hormone Receptor Expression In the Granulosa Cellsmentioning
confidence: 99%
“…IL-6 inhibited FSH-induced LHR expression in rat and porcine GCs (40,41) and suppressed FSH-induced steroidogenesis in rat and bovine GCs (42, 43). Although a report indicated that IL-6 enhanced FSH-induced LHR expression in rat GCs (44), excess IL-6 is commonly associated with aging and believed to affect follicular development negatively (45)(46)(47).…”
Section: Folliculogenesis In the Ovarian Cortexmentioning
confidence: 99%
“…GCs from eCG-primed rats were harvested as described previously (14). Cells (2´10 5 cells / well) were plated onto a 24-well tissue culture dish (Asahi Techno Glass, Tokyo) coated with collagen type I in 0.5 ml chemically defined medium [serum-free Dulbecco's Modified Eagle's Medium (Gibco BRL, Grand Island, NY, USA) supplemented with 5 m g / ml transferrin, 40 ng / ml hydrocortisone, 4 mg / ml BSA, 30 ng / ml androstendione, 1 mg / ml fibronectin, 4 m g/ ml insulin, 100 ng / ml FSH, and 10 ng / ml LH] in the absence or presence of T 3 (10 -9 -10 -5 M).…”
Section: Gcs Preparation and Culturementioning
confidence: 99%